Silicon Enhances Banana Resistance to Fusarium oxysporum f.sp. cubense through Ethylene Signaling Modulation and Root Tissue Protection - Pambudi, Arief; Effendi, Yunus; Sudirman, Lisdar I; Miftahudin (HAYATI Journal of Biosciences, 2026)
Fusarium oxysporum f.sp. cubense Tropical Race 4 (Foc TR4) is an agent of banana's vascular wilt that severely hampers production. It has been indicated that silicon (Si) might play a role in plant defense, but the banana–Foc pathosystem mechanism needs to be investigated. This study aimed to assess the impact of Si supplementation on banana plant responses to Foc infection, particularly using a completely randomized design arranged in four treatments: Control, Foc, Si, and Si*Foc. The transcript levels of the ethylene-receptor (EIN1, EIN3), ethylene-response factor (ERF1, ERF2), and the defense marker PR4 were quantified using qRT-PCR. Phenotypic observation, corm lesion severity, and root anatomy were also evaluated. Results indicated that early ethylene signaling (EIN1, EIN3) was down-regulated, and ERF2 was up-regulated in the presence of Si during Foc infection. Foc-infected plants treated with Si displayed smaller lesion areas, greater root structural stability, and less aerenchyma formation. Plant growth reduction caused by Foc was also relieved by Si, showing increased root-to-shoot biomass ratios and modified leaf shape. Multivariate analysis validated differences in physiological and transcriptional patterns in Si*Foc plants. These results indicate that Si improves banana resistance to Foc by regulating ethylene-mediated defense, tissue integrity, and stress resistance.